2018
DOI: 10.3390/su10124665
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Value of Investment in Real Estate: Real Options Approach

Abstract: The issue of application of real option valuation approach in the valuation of investment project is presented in the article in a way in which the flexibility of the project could be included in the process of its valuation. The authors apply the valuation approach in case of a specific investment project in the real estate in the capital city of the Czech Republic—Prague, using the option to expand, to contract, and to abandon the project. The main aim of this case study is to present a practical application… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Our study focuses on examining the investment decision-making process at the individual level. We join the emerging and promising stream of studies that utilize experimental laboratory designs to closely investigate decision-making behavior in a real options based mechanism [12][13][14][15][16][17]. By doing so, we contribute to the managerial literature regarding micro-foundations of investment decision-making under uncertainty.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study focuses on examining the investment decision-making process at the individual level. We join the emerging and promising stream of studies that utilize experimental laboratory designs to closely investigate decision-making behavior in a real options based mechanism [12][13][14][15][16][17]. By doing so, we contribute to the managerial literature regarding micro-foundations of investment decision-making under uncertainty.…”
Section: Discussionmentioning
confidence: 99%
“…In this journal, the use of real options has been discussed a number of times in connection with economic sustainability. Focus has been on economic evaluation in the context of public private partnerships [12][13][14], technology, research, and development investments [15,16], investment in real-estate [17], and environmental investments [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…An abandonment option is only exercised if the gain is greater than the present value of expected cash flows until the end of the investment project's useful life [99]. Thus, real probabilities of the abandonment option being exercised were considerably higher for both investment projects (Figure 7), which demonstrated that, with greater probability, the value generated by projects' cash flows did not exceed the value of abandoning them.…”
Section: Stochastic Modelmentioning
confidence: 98%
“…In the project with land purchase, the low probability of exercising the option to expand (8%) explained why valuation was lower compared to the other options (Figure 6B). When indicating non-expansion, it means that the present value of the project's expected cash flows, if expanded, would not exceed the additional disbursement needed to finance the expansion [99]. This means that when the project has a negative value, it does not obtain any value from the option to expand.…”
Section: Stochastic Modelmentioning
confidence: 99%
“…Also, the work of [30] incorporated put option pricing to determine whether the global real estate market was undervalued in 18 countries after the Asian financial crisis, whereas the work of [31] confirmed the undervalued real estate market in the 500 real estate categories in 19 countries through the put option. Furthermore, the works of [32,33] utilized the real option to discover the real estate bubble in Hong Kong and Thailand; the works of [34,35] assessed the appropriate level of land prices in Japan through real options and confirmed the existence of a bubble; and the work of [36] and that of [37] utilized the options approach to identify the real estate bubbles in Latvia and the Czech Republic, respectively. In summary, the options approach can reflect the uncertainty of real estate investors more effectively than the traditional discounted cash flow or net present value analysis [38,39].…”
Section: Introductionmentioning
confidence: 99%